Lentera: Inovasi Platform Edukasi Adaptif Berbasis AI dan Karakter Islami dengan Fitur Mikro-Sosial Aman untuk Menangkal Disinformasi dan Membangun Generasi Melek Etika Digital - Muh. Fatih Ahsan Maulana (PT. Willy Print Art, 2025)
The development of digital technology in the world of education provides many opportunities, but also poses new challenges, especially in terms of ethics, the spread of misinformation, and weak character formation in the online learning process. In the midst of the increasingly rapid flow of digitalization, learning is often purely cognitive and pays little attention to moral, spiritual, and social values ​​that are important for the growth of students. To answer these problems, an innovation called LENTERA (National Education Service Guided by Artificial Intelligence Friendly Ethics) was developed. This innovation was developed through a technology development approach with a system design method based on literature studies and user needs. LENTERA is an adaptive learning platform that combines technology with the instillation of Islamic character values ​​and a safe digital social interaction space. This platform has main features such as detecting students' emotional conditions, value-based learning materials, hoax recognition tools, and closed discussion spaces between students. LENTERA aims not only to improve the quality of online learning, but also to form students who are intelligent, ethical, and critical of information. This innovation is expected to be able to support the creation of an inclusive, humane, and character-based digital education ecosystem, in accordance with the challenges of education in the modern era.